Effects of a psychological intervention on the quality of life of obese adolescents under a multidisciplinary treatment - Camila R.M. Freitas; Thrudur Gunnarsdottir; Yara L. Fidelix; Thiago R.S. Tenório; Mara C. Lofrano-Prado; James O. Hill; Wagner L. Prado
Abstract Objective: To investigate the effects of multidisciplinary treatment with and without psychological counseling on obese adolescents' self-reported quality of life. Methods: Seventy-six obese adolescents (15.87 ± 1.53 y) were allocated into psychological counseling group (PCG; n = 36) or control group (CG; n = 40) for 12 weeks. All participants received the same supervised exercise training, nutritional and clinical counseling. Participants in PCG also received psychological counseling. QOL was measured before and after 12 weeks of intervention by Generic Questionnaire for the Evaluation of Quality of Life (SF-36). Results: The dropout rate was higher in GC (22.5%) when compared with PCG (0.0%) (p < 0.001). After 12 weeks, participants from PCG presents lower body weight, relative fat mass and higher free fat mass (p < 0.001 for all) compared to GC. QOL improved among adolescents from both groups (p < 0.05), however, a better QOL was reported from those adolescents enrolled in PCG. Conclusion: The inclusion of a psychological counseling component in multidisciplinary treatment for adolescent obesity appears to provide benefits observed for improved QOL as compared with treatment without psychological counseling.